Australian Perspective of Transportation and Taxation: A relationship but no marriage - Pearce, Prafula (2010)
This article examines whether there is a harmonious relationship between the transportation and tax policy in Australia and whether a change in tax policy is required to promote the use of more fuel efficient vehicles, vehicles using cleaner fuels, a reduction in the use of vehicles and reduction in congestion. In this article a case is made for the introduction of tax measures in order to lead to a new way of thinking about energy. The tax should relate to the power and weight of the vehicle and its use and not where the vehicles are manufactured. A new way of thinking is required as it takes millions of years for our planet to produce fossil fuel, but it takes an instant to burn it, and once burnt, it is irrecoverable. Therefore the Australian Government should take the responsibility and implement appropriate taxation policies to promote the efficient movement of people and goods with the least consumption of liquid oil. Taking into consideration the outcome of the recent review of Australia’s Future Tax System , this paper explores whether a different form of road vehicle taxation would be more appropriate to 21st century environmental, transport and fiscal needs than the 20th century regime of taxing road vehicle purchase, ownership and the fuel that the vehicles use. Tax can, and arguably should, be used more progressively and more creatively to change societal behaviour towards sustainable transportation needs. A true marriage is required between transportation and tax policy, not just a marriage of convenience.